1989
DOI: 10.1007/bf01963779
|View full text |Cite
|
Sign up to set email alerts
|

Influenza subtype-specific immunoglobulin A and G responses after booster versus one double-dose vaccination in hemodialysis patients

Abstract: The antibody response in hemodialysis patients was studied after one double dose of influenza vaccine versus one conventional dose plus a booster dose five weeks later. The influenza virus subtype specific IgA and IgG responses were recorded by means of an indirect immunofluorescence assay over a period of 20 weeks. Higher antibody titers, higher response rates and a higher rate of development of protective titers after the single double-dose vaccine indicated it was superior to the single dose/booster dose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…Previous influenza vaccination studies with dialysis patients have shown that their responses are weaker than those of subjects with a normal kidney function [2, 14, 15]. With enhanced vaccination protocols, it has, however, been possible to induce better responses than with conventional vaccination schedules [16], indicating quantitative rather than qualitative immune abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous influenza vaccination studies with dialysis patients have shown that their responses are weaker than those of subjects with a normal kidney function [2, 14, 15]. With enhanced vaccination protocols, it has, however, been possible to induce better responses than with conventional vaccination schedules [16], indicating quantitative rather than qualitative immune abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tuberculosis is increased by up to 10-to 12-fold (Andrew et al 1980;Rutsky & Rostana 1980). There is also a significantly increased incidence of fungal and viral infections (Broyer & Boudouillez 1985;Eickhoff et al 1961;Fe1dhoff et al 1981;Onorato et al 1979;Plotkin et al 1990;Rautenberg et al 1989;Sipilsa et al 1990). …”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…ESKD patients awaiting transplantation are immunologically unique in showing features of both immunodeficiency (22)(23)(24) and chronic inflammation/immune dysregulation (25)(26)(27). ESKD patients have reduced peripheral blood Tregs (28) and naïve T cells (29), implying a deficiency of naïve Tregs, the population most resistant to Th17 conversion in vitro (14).…”
Section: Introductionmentioning
confidence: 99%